Circadian nuclear receptor Rev-erbalpha is expressed by platelets and potentiates platelet activation and thrombus formation. (3rd October 2022) - Shi, J; Tong, R; Zhou, M; Gao, Y; Zhao, Y; Chen, Y; Liu, W; Li, G; Lu, D; Meng, G; Hu, L; Yuan, A; et al.
Abstract: Background: Adverse cardiovascular events have day/night patterns with peaks in the morning, potentially related to endogenous circadian clock control of platelet activation. Circadian nuclear receptor Rev-erbα is an essential and negative component of the circadian clock. Purpose: We aim to investigate the expression profile and biological function of Rev-erbα in platelets. Methods and results: Here we report the presence and functions of circadian nuclear receptor Rev-erbα in human and mouse platelets. Both human and mouse platelet Rev-erbα showed a circadian rhythm that positively correlated with platelet aggregation. Global Rev-erbα knockout and platelet-specific Rev-erbα knockout mice exhibited defective in hemostasis as assessed by prolonged tail-bleeding times. Rev-erbα deletion also reduced ferric chloride-induced carotid arterial occlusive thrombosis, prevented collagen/epinephrine-induced pulmonary thromboembolism, and protected against microvascular microthrombi obstruction and infarct expansion in an acute myocardial infarction model. In vitro thrombus formation assessed by CD41-labeled platelet fluorescence intensity was significantly reduced in Rev-erbα knockout mouse blood. Platelets from Rev-erbα knockout mice exhibited impaired agonist-induced aggregation responses, integrin αIIbβ3 activation and α-granule release. Consistently, pharmacological inhibition of Rev-erbα by specific antagonists decreased platelet activation markers in both mouse and human platelets. Mechanistically, mass spectrometry and co-immunoprecipitation analyses revealed that Rev-erbα potentiated platelet activation via oligophrenin-1-mediated RhoA/ERM (ezrin/radixin/moesin) pathway. Conclusion: We provide the first evidence that circadian protein Rev-erbα is functionally expressed in platelets and potentiates platelet activation and thrombus formation. Rev-erbα may serve as a novel therapeutic target for managing thrombosis-based cardiovascular disease. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): This work was supported by grants from the National Science Fund for Distinguished Young Scholars (81625002), the National Natural Science Foundation of China (81930007).